THE COMPARISON OF OUTCOMES AFTER LAPAROSCOPIC MYOMECTOMY WITH THE USE OF DIFFERENT UTERINE SUTURE TECHNIQUES - B. Habrat; O. Lytvak; B. Lysenko; A. Habrat (Клінічна та профілактична медицина, 2020)
Purpose: to improve the outcomes and speed up the recovery after laparoscopic myomectomy in females with uterine leiomyoma, based on the comprehensive study and comparison of different uterine suturing techniques.